ANALISIS FRAUD DIAMOND DALAM MENDETEKSI KECURANGAN LAPORAN KEUANGAN - Purwitasari, Afrida; Setiawati, Erma (Widya Balina, 2023)
Financial statement fraud is a legal strategy employed to manipulate financial statements by exploiting various loopholes in regulations, engaging in transactions with the primary objective of presenting a misleading financial picture. This study aims to assess the impact of pressure, opportunity, rationalization, and capability on financial statement fraud within manufacturing companies listed on the Indonesia Stock Exchange during the period 2020-2022. The research utilized purposive sampling, involving 160 companies that met the specified criteria. Multiple linear regression analysis was employed as the analytical method. The empirical findings reveal that both pressure and rationalization significantly influence financial statement fraud. In contrast, opportunity and capability show no significant effect on financial statement fraud.